2021
DOI: 10.2147/cia.s306982
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in an Aging Society – Role of Oxidant-Antioxidant Imbalance and Inflammation Markers in Disentangling Atherosclerosis

Abstract: Introduction:The prevalence of metabolic syndrome among the elderly population is growing. The elements of metabolic syndrome in an aging society are currently being researched. Atherosclerosis is a slow process in which the first symptoms may be observed after many years. The mechanisms underlying the progression of atherosclerosis are oxidative stress and inflammation. Inflammation and oxidative stress are associated with the increased incidence of metabolic syndrome. Taking the above into consideration, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 144 publications
1
14
0
Order By: Relevance
“…Increased reactive oxygen species (ROS) causes vasoconstriction and encourages arterial hypertension, promotes the formation of atherosclerotic plaques, and causes vascular endothelial dysfunction 44. The accumulation of ROS leads to sarcopenia by promoting muscle hydrolysis; at the same time, it affects muscle protein synthesis via nitrification 48. In addition, high palmitic acid intake leads to muscle atrophy49 and CVD50 through increasing ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased reactive oxygen species (ROS) causes vasoconstriction and encourages arterial hypertension, promotes the formation of atherosclerotic plaques, and causes vascular endothelial dysfunction 44. The accumulation of ROS leads to sarcopenia by promoting muscle hydrolysis; at the same time, it affects muscle protein synthesis via nitrification 48. In addition, high palmitic acid intake leads to muscle atrophy49 and CVD50 through increasing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…44 The accumulation of ROS leads to sarcopenia by promoting muscle hydrolysis; at the same time, it affects muscle protein synthesis via nitrification. 48 In addition, high palmitic acid intake leads to muscle atrophy 49 and CVD 50 through increasing ROS. These mechanisms are involved in SI and subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome has become one of the most common chronic diseases in the elderly (3) . Some studies have shown that metabolic syndrome and its components are important factors in the progression of atherosclerotic disease in the elderly (4) . A metabolic syndrome is a group of metabolic disorders with unknown molecular mechanisms.…”
mentioning
confidence: 99%
“…In several cases, diabetes occurs in association with other diseases such as obesity, hypertriglyceridemia, and arterial hypertension. These are some of the main components of metabolic syndrome [ 24 , 25 ]. Nearly 90% of individuals with T2DM are overweight or obese.…”
Section: Discussionmentioning
confidence: 99%